NbSOBIR1 Partitions Into Plasma Membrane Microdomains and Binds ER-Localized NbRLP1 - Li, Yi-Hua; Ke, Tai-Yu; Shih, Wei-Che; Liou, Ruey-Fen; Wang, Chao-Wen (Frontiers in Plant Science, 2021)
The receptor-like kinase SOBIR1 binds various receptor-like proteins that perceive microbe-associated molecular patterns (MAMPs) at the plasma membrane, which is thought to activate plant pattern-triggered immunity (PTI) against pathogen invasion. Despite its potentially crucial role, how SOBIR1 transmits immune signaling to ultimately elicit PTI remains largely unresolved. Herein, we report that a Nicotiana benthamiana gene NbRLP1, like NbSOBIR1, was highly induced upon Phytophthora parasitica infection. Intriguingly, NbRLP1 is characterized as a receptor-like protein localizing to the endoplasmic reticulum (ER) membrane rather than the plasma membrane. Using bimolecular fluorescence complementation and affinity purification assays, we established that NbRLP1 associates with NbSOBIR1 likely through the contact between the ER and plasma membrane. We further found that NbSOBIR1 at the plasma membrane partitions into mobile microdomains that undergo frequent lateral movement and internalization. Remarkably, the dynamics of NbSOBIR1 microdomain is coupled to the remodeling of the cortical ER network. When NbSOBIR1 microdomains were induced by the P. parasitica MAMP ParA1, tobacco cells overexpressing NbRLP1 accelerated NbSOBIR1 internalization. Overexpressing NbRLP1 in tobacco further exaggerated the ParA1-induced necrosis. Together, these findings have prompted us to propose that ER and the ER-localized NbRLP1 may play a role in transmitting plant immune signals through regulating NbSOBIR1 internalization.